1980
DOI: 10.1111/j.1432-1033.1980.tb04846.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis of Rat Erythrocytes by Replacement of the Natural Phosphatidylcholine by Various Phosphatidylcholines

Abstract: Vesicles of a variety of types of phosphatidylcholine have been shown to be suitable donors of phosphatidylcholine to intact rat erythrocytes in the presence of a specific phosphatidylcholine exchange protein. Coincident with the progression of phosphatidylcholine exchange is the onset of hemolysis, occurring at degrees of exchange characteristic for the type of phosphatidylcholine employed. During exchange with the dimyristoyl, dipalmitoyl and distearoyl species, hemolysis starts when 27 %, 25 % and 22 % of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

1981
1981
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…A similar observation has been made before with rat erythrocytes [16], although in this case hemolysis started already after 20% replacement. Rat erythrocyte PC contains, however, a high content (35%) of disaturated species, whereas in human erythrocytes only 13% of the total PC is present in the disaturated form.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar observation has been made before with rat erythrocytes [16], although in this case hemolysis started already after 20% replacement. Rat erythrocyte PC contains, however, a high content (35%) of disaturated species, whereas in human erythrocytes only 13% of the total PC is present in the disaturated form.…”
Section: Discussionsupporting
confidence: 87%
“…Since extensive modifications are impossible to obtain in vivo, an in vitro approach has been applied. Recently, Lange et al [16] used the phosphatidylcholine specific transfer protein of bovine liver to modify the molecular species composition of PC in the rat erythrocyte membrane and it was observed that an increase in the degree of saturation of the phosphatidylcholine in this membrane resulted in hemolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Freeze-fracture electron micrographs show the evaginations of the membrane in detail [35]. When exchange was continued spherocytes were formed ( fig.(i).…”
Section: Replacement Of Membrane Phospholipid By Exchange Proteinmentioning
confidence: 99%
“…During the exchange reaction 10-20% of the native erythrocyte PC was replaced by donor PC. In order to prevent modification of the fatty acyl composition of the erythrocyte PC [15] in the transbilayer movement studies, the (14C)PC trace was embedded in most experiments in a matrix of egg PC, which has a fatty acyl composition that resembles that of the human erythrocyte. Because peroxidation of PC was reported to induce transbilayer movement of phospholipids in model membranes [29], we also checked the degree of peroxidation of the egg PC.…”
Section: :Jcbmentioning
confidence: 99%
“…In previous studies [l 1,15, 161 it was shown that defined PC species can be introduced into the outer monolayer of intact erythrocytes by means of the PCspecific phospholipid exchange protein [17]. In the present study this technique was combined with the use of phospholipases to hydrolyze the outer monolayer [18].…”
mentioning
confidence: 99%